PENGARUH KOMITMEN ORGANISASI, PARTISIPASI DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA PT. BANK LIPPO Tbk CABANG KUDUS - Yenny Verawati; Joko Utomo (Universitas Muria Kudus, 2011)
The main objective of this study is 1). Are there influense on organisation commitment, participation, and motivation as partial and multiple to work performance PT Bank Lippo Tbk Unit of Kudus. 2) To find what the most influense variable to work performance PT Bank Lippo Tbk. Unit of Kudus. The respondents of this study are 43 employee of PT Bank Lippo Tbk Unit of Kudus. Analysis technique is used Partial Regression. The results of this research show that as partial variable organization commitment and motivation are influence on work performance, but participation variable not influense on work performance. Results of hipotesis test show that t test value organization commitmet and motivation variable are 2,912 and 1,166 the most that t tabel 2,021. So result of hipotesis test show that t test value participation variable -1,148 the lest from t tabel 2,021. The multiple variable organization commitment, participation and motivation are influense on work performance. Result of hipotesis test show that F test value 4,504 the most that F test tabel of 2,839. The most influense variable to work performance PT Bank Lippo Tbk Unit of Kudus is motivation variable